Soaking and Cooking Techniques: A Study on Nutritional Enhancement of Common Beans (Phaseolus vulgaris L.) in Libyan Cuisine - M. Abdel-Gader , Zienab; Al-Ghatmi , Najat; A. Sharif , Abubaker; Al-kamoushy, Zenab (Scientific Journal of University of Benghazi, 2024)
This study investigates the effect of soaking duration, cooking time, and the type of water used on the mineral and nutritional content of common beans (Phaseolus vulgaris L.) available in the Libyan market. Common beans are a significant source of essential minerals, making them a staple food in Libya. The research involved preparing beans through various methods: uncooked (control), unsoaked, boiled in desalinated water, and soaked for 12 hours in four different types of water (distilled, desalinated, artificial river, and well water) before boiling. Samples were measured using a flame atomic absorption spectrophotometer. The results demonstrated that soaking beans significantly reduced cooking time and enhanced the retention of vital minerals. The concentrations of minerals (mg/100 ml) in the cooked beans were as follows: sodium (Na) ranged from 2.8 to 49.3, calcium (Ca) from 8.4 to 20.8, potassium (K) from 189.0 to 742.8, zinc (Zn) from 1.1 to 2.1, barium (Ba) from 159.1 to 300.9, and iron (Fe) from 1.2 to 37.7, depending on the soaking and cooking conditions. Additionally, the type of water used for soaking and cooking influenced the mineral content, with artificial river and well water yielding higher concentrations of beneficial nutrients such as Na ranged from 400 to 628 mg/100 ml and Ca ranged from 50 to 73 mg/100 ml. The measured concentration of heavy metals in the samples is low and falls within the normal range according to the Libyan food specifications. This research contributes to the understanding of how traditional cooking practices can be improved for better health outcomes. The findings highlight the importance of proper soaking and cooking techniques in maximizing the nutritional value of common beans, providing practical recommendations for consumers and food preparers.